2007 IEEE 10th International Conference on Rehabilitation Robotics 2007
DOI: 10.1109/icorr.2007.4428439
|View full text |Cite
|
Sign up to set email alerts
|

Integration of an Intelligent Decision Support System and a Robotic Haptic Device for Eye-Hand Coordination Therapy

Abstract: This paper is the continuation of a work presented at ICORR 05, in which the results of single-subjects studied suggested that the haptic robotic therapy proposed improved eye-hand coordination in children diagnosed with this problem, using a robotic mapping from a haptic user interface to a virtual environment. This paper presents the integration of the aforementioned system with an intelligent decision support system (IDSS) based on fuzzy-logic. Our goal is to develop an assessment and training procedure tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…One of the trends in the development of robotics is human-robot interaction involving communications with people through speech, gestures, and facial expressions by applying biometric technologies. Various DSS are being developed (Weiss and Yung 2009;Mouaddib 2008;Johannsen 2007;Nieten and Fishwick 2007;Pernalete et al 2007;Heikkilä et al 2013;Patel and Kamrani 1996). These systems are being integrated with robot technologies.…”
Section: Robotic Decision Support Systemsmentioning
confidence: 98%
“…One of the trends in the development of robotics is human-robot interaction involving communications with people through speech, gestures, and facial expressions by applying biometric technologies. Various DSS are being developed (Weiss and Yung 2009;Mouaddib 2008;Johannsen 2007;Nieten and Fishwick 2007;Pernalete et al 2007;Heikkilä et al 2013;Patel and Kamrani 1996). These systems are being integrated with robot technologies.…”
Section: Robotic Decision Support Systemsmentioning
confidence: 98%
“…Despite the fact that most of the preceding works have used haptic devices for rehabilitation, none of them has implemented any autonomous decision making system for assessing the patient's performance. However, an interesting work was presented by [14] where an intelligent decision support system based on fuzzy logic is used in handeye coordination therapy. The system takes haptic data from previous tests performed by the subject and uses them to make decision about the complexity of the next test to be performed.…”
Section: Related Workmentioning
confidence: 99%
“…Bouri et al in [25] presented an innovative haptic device designed specifically for the rehabilitation of hemiplegic children, which activates their hand joints, similarly to MT. In [26] and [27], the authors investigated about new haptic technologies to overall problems with handwriting or drawing due to graphomotor issues; they designed technologies and the protocol for the assessment and therapy for eye-hand coordination. Ferre et al, as reported in [28], realized a haptic framework that captures and mimics manual therapy techniques using a multifinger device.…”
Section: Introductionmentioning
confidence: 99%